The Existence Of The National Land Agency In Indonesia As A Drafter, Manager, And Executor Of National Land Policy - Ma'ruf, Umar; Karjoko, Lego; Handayani, Tri Astuti; Handayani, I Gusti Ayu Ketut Rachmi (The journal of contemporary issues in business and government, 2021)
The existence of the National Land Agency began in 1988 with Presidential Decree Number 26 of 1988. Institutions dealing with land in Indonesia actually existed and started in 1951 under the State Ministry of Agrarian Affairs's name and subsequently changed its characters, but still use the word "Agrarian" within the institution. Only in 1988, the National Land Agency came up. In Presidential Decree No 26 of 1988, there are six functions of BPN (National Land Agency) that lead to policy formulation and planning of land tenure and use. The existence of the National Land Agency shall be regulated continuously following the development of the existing conditions in the amendment of a presidential decree in 1999, 2000, 2001, and 2006 and by presidential regulation in 2013. Presently, the National Land Agency's existence is based on Presidential Regulation No. 20 of 2015 Based. On Presidential Regulation No. 20 of 2015, BPN (National Land Agency) has ten functions covering as a drafter, regulator, and executive of land policy ex officio headed by Minister of Agrarian and Spatial.